Perjanjian Kerja Sama Program Gerakan Sekolah Menulis Buku Nasional - I Wayan Yudi Antara Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2022)
In the implementation of economic development, the economy has an important role and importance as a supporting factor for the success of national development, and maintaining cooperation in efforts to expand the scale of economic development is the most important asset. With the background of the above problems, some questions can be considered as follows: Characteristics of a Cooperation Agreement How the school movement program wrote a national book between PT Nyala Masa Depan Indonesia and SMP Negeri 1 Denpasar, and what if there was a Cooperation Agreement between PT Nyala Masa Depan Indonesia and SMP Negeri 1 Denpasar A school movement program has been established to write books nationally. The method used is a normative legal search using primary and secondary legal sources. The results of this survey state: The characteristics of the cooperation agreement between PTs. Indonesian Future Light and SMP Negeri 1 Denpasar use a standard agreement. The contract model is in the form of a written contract. The failure of the cooperation agreement between PT. Nyala Masa Depan and SMP Negeri 1 Denpasar are carried out through non-procedural processes and processes. Of the two options exercised by the disputing parties, there is non-jurisdiction (arbitration).